The Role of Social Media During Protests on Maidan - Grażyna Piechota; Robert Rajczyk (Communication Today, 2025)
Political protests which took place in Ukraine were another example of how social and content websites were used during protests on the Independence Square (Maidan Nezalezhnosti) in Kiev – the protests started in November 2013 and ended in February 2014. This article offers presentation of the results of research that was carried out in Kiev and Lviv in May 2015 among students of two Ukrainian universities: Borys Grinchenko Kyiv University and the National University of Taras Shevchenko in Lviv. The aim of the conducted research was to establish which of the new media (social media and blogs) and in what way were used by the students during protests and if the way of using the new media influenced the engagement of students in protests. Such comparative research also made it possible to find differences in attitudes and motivations of students participating in protests in Kiev but coming from two different cities in Ukraine – Kiev and Lviv. The research results may contribute to a deepened analysis of the ways the new media are used during political and social protests with reference to differences in people’s attitudes depending on their personal or Internet engagement.